Tuberculosis transcriptomics: host protection and immune evasion mechanisms - Ozturk, Mumin (Institute of Infectious Disease and Molecular Medicine, 2018)
Mycobacterium tuberculosis (Mtb) is the leading cause of death from an infectious disease. The success of the pathogen lies in its ability to subvert hostile intracellular macrophage environment. We performed genome-wide transcriptional deep sequencing on total RNA in murine bone marrow-derived macrophages (BMDM) infected with hypervirulent Beijing strain (HN878) in an extensive time kinetic manner using single molecule sequencer and cap analysis gene expression (CAGE) technique. CAGE analysis revealed nearly 36000 unique RNA transcripts with approximately 16000 are not unannotated to a specific gene. This thesis addressed global changes in RNA expression levels in macrophages infected with Mtb in a time kinetic manner to pinpoint novel host protection and immune evasion genes and elucidate the role of these genes in vitro macrophage assays and in vivo knockout mouse studies. The data in this thesis showed that basic leucine zipper transcription factor 2 (Batf2) was an important factor that regulates inflammatory responses in Mtb infection. Deletion of Batf2 led to the survival of mice with reduced lung inflammation and histopathology due to reduced recruitment of inflammatory macrophages. We also showed that Batf2 was highly expressed in peripheral blood from adolescents who progressed from infection to tuberculosis disease and a predictive human biomarker for tuberculosis disease. In contrast to Batf2, we showed that Protein Kinase C-delta (PKC-δ) deficient mice are highly susceptible to tuberculosis and human lung proteomics dataset revealed that PKC-δ was highly upregulated in the necrotic and cavitory regions of human granulomas in multi-drug resistant subjects. PKC-δ deficient mice had a significant reduction in alveolar macrophages and dendritic cells, reduced accumulation of lipid bodies and serum fatty acids. In vitro experiments showed that PKCδ was required for optimal killing effector functions which were independent of phagosome maturation and autophagy in primary murine macrophages. Our studies suggested that these novel genes play a role in the immune response to Mtb and should be studied more thoroughly to evaluate their potential in possible TB interventions.